Walisanga: Asal, Wilayah dan Budaya Dakwahnya di Jawa - Siti Maziyah; Rabith Jihan Amaruli (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2020)
Islamization in Java in the 15th century to the 16th century is inseparable from the role of Walisanga. According to local Javanese beliefs, they numbered nine people. Most of their da'wah areas are in East Java, then in Central Java, and in West Java. Why is that? Where are they from? How does Walisanga carry out its mission so that the Javanese are still close to the nine saints and their graves are still frequently visited? The writing of this article uses a historical approach, starting with the study of literature, which looks for books and articles relating to the origin, territory and propaganda of Walisanga. Next, each data is arranged into several topics to answer the problem. The results showed that the nine people who joined Walisanga were all descendants of foreigners from various Islamic countries. They were missionaries who could be closer to the Javanese government. In carrying out their da'wah, they use a cultural approach, both through the fields of social economy, education, marriage, art, and politics.